Samantha Jane's missing smile a story about coping with the loss of a parent - Kaplow, Julie B. 1974- (Magination Press, 2007)
With the help of her neighbor Mrs. Cooper, Samantha Jane is able to talk about how sad she is since her father died, and then she begins to feel better.